Origins and evolution of the dual functions of strigolactones as rhizosphere signaling molecules and plant hormones. (February 2022) - Kyozuka, Junko; Nomura, Takahito; Shimamura, Masaki
Abstract: Strigolactones (SLs) play roles as a class of plant hormones and rhizosphere signaling chemicals that induce hyphal branching of arbuscular mycorrhizal fungi and seed germination of parasitic plants. Therefore, SLs have dual functions. Recent progress in genome sequencing and genetic studies of bryophytes and algae has begun to shed light on the origin and evolution of these two functions of SLs.